Double acting Stirling engine: Modeling, experiments and optimization. (1st December 2015) - Féniès, Gwyddyon; Formosa, Fabien; Ramousse, Julien; Badel, Adrien
Highlights: An equivalent electrical network model of a free piston Stirling engine is proposed. The model accounts for the gas, mechanical dynamics and global energy equilibrium. A comparison between theoretical and experimental data is performed. Energy and exergy analysis underline the main losses and optimization are proposed. A 170 cm 3 displacement 3-phase optimized engine makes in theory 18 W at 25 Hz. Abstract: A three phase free piston type double acting Stirling engine model is proposed and validated using experimental results. The modeling strategy is based on a combination of two sub-models: a global thermal model of the engine to deal with heat sources coupling and a detailed equivalent electrical network model which accounts for the gas and mechanical dynamic physics of the engine. Derived features, such as the amplitude, the frequency, the compression and the expansion powers are then finally obtained. The model is experimentally validated with a prototype of a free piston Stirling engine. Mean error on the amplitude, the frequency, the internal temperatures and the compression and expansion powers is 9%, so the model is considered accurate enough to predict performances. For optimization purpose, a numerical analysis is performed selecting the three following critical parameters: (i) dead volume of the chambers, (ii) natural frequency of the mechanical oscillators and (iii) thermal conduction between hot and cold sides. Smaller dead volume, large oscillating mass and high insulation are to be sought for maximizing the performances. With a pressurization of 3 bar, a theoretical useful power of 18 W can be reach with conservative modification of the existing prototype. Moreover, energy and exergy analyses highlight the main losses in the system: thermal leakage, gas spring hysteresis as well as heat transfer and viscous dissipation in the heat exchangers.